Bifidobacterium exopolysaccharides: new insights into engineering strategies, physicochemical functions, and immunomodulatory effects on host health - Sadeghi, Mahsa; Haghshenas, Babak; Nami, Yousef (Frontiers in Microbiology, 2024)
Bifidobacteria are a prominent type of bacteria that have garnered significant research attention for their exceptional probiotic properties and capacity to produce exopolysaccharides (EPSs).These compounds exhibit diverse physical, chemical, and biological characteristics, prompting numerous investigations into their potential applications. Researchers have noted their beneficial effects as immune modulators within the host's body across various industries. Extensive research has been conducted on the immunomodulatory effects of bifidobacteria-derived EPSs, with emerging engineering strategies aimed at enhancing their immune-modulating capabilities.Understanding the structure, physicochemical properties, and biological activities of these compounds is crucial for their effective utilization across different industries. Our review encompassed numerous studies exploring Bifidobacterium and its metabolites, including EPSs, across various sectors, drawing from diverse databases. The distinctive properties of EPSs have spurred investigations into their applications, revealing their potential to bolster the immune system, combat inflammation, and treat various ailments. Additionally, these compounds possess antioxidant and antimicrobial properties, making them suitable for incorporation into a range of products spanning food, health, and medicine.